2003
DOI: 10.1007/s00464-002-8907-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraabdominal abscess following open and laparoscopic appendectomy in the pediatric population

Abstract: This study demonstrates no statistically significant difference in the rate of IAA among children following LA and OA. LA can be performed for perforated appendicitis without increasing the risk of IAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 13 publications
1
33
1
Order By: Relevance
“…Ortega et al [18] observed IAA in six of 167 patients after LA (five of them had nonperforated appendicitis) but none after OA. In contrast, McKinlay et al [15] found no significant difference in the rate of IAA after LA and OA. A high rate of IAA after LA may be explained by the fact that the appendix is usually transected inside the abdomen, increasing the risk of peritoneal contamination [13,18].…”
Section: Discussionmentioning
confidence: 89%
“…Ortega et al [18] observed IAA in six of 167 patients after LA (five of them had nonperforated appendicitis) but none after OA. In contrast, McKinlay et al [15] found no significant difference in the rate of IAA after LA and OA. A high rate of IAA after LA may be explained by the fact that the appendix is usually transected inside the abdomen, increasing the risk of peritoneal contamination [13,18].…”
Section: Discussionmentioning
confidence: 89%
“…The similarity in 28-day readmission rates between the two techniques supports the assertion that early complication rates were comparable between groups. Despite the concerns over higher rates of intra-abdominal abscess formation after laparoscopy in adults [12], several studies in children have not demonstrated a significant difference between the techniques in this regard [4,6].…”
Section: Discussionmentioning
confidence: 98%
“…Concerns have been raised however over increased rates of intra abdominal abscess [4] and longer operating times [2,6] associated with the laparoscopic approach. More recent studies have however demonstrated a reduction in surgical time with increasing surgical experience [7].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with CA, the laparoscopy is more advantageous in terms of length of stay, nasogastric tube, requirement of analgesia, superficial surgical site infection and requirement of reoperation. There is no statistical difference between LA and OA groups according to the IA both in CA and NCA patients as in some other studies (15,16 Table 3. The mean values of parameters in complicated appendicitis groups in children with LA.…”
Section: Discussionmentioning
confidence: 55%